2008
DOI: 10.21704/rea.v7i1-2.355
|View full text |Cite
|
Sign up to set email alerts
|

Especies Arbóreas Evaluadas Como Bioacumuladoras De Azufre en La Ciudad De Chihuahua, México

Abstract: ResumenLa sustentabilidad de las ciudades debe basarse en gran medida por el capital ecológico que representa la vegetación, ya que constituye una alternativa para el estudio de la contaminación ambiental. Con el objetivo de determinar la capacidad de acumulación de azufre en cinco especies arbóreas fueron tomadas muestras de material foliar de 225 árboles ubicados en la ciudad de Chihuahua conforme a los usos de suelo comercial y servicio, industria mixta, industria pesada, residencial clase media-alta y resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…One source of Pb is the resuspension of Pb [58], where it can accumulate in places such as windows, sidewalks, balconies, etc. This aspect should be taken into account when studying the influence that Pb can have on health since it is a highly toxic element and has no function in any organism [10]. To reduce this risk, a cleaning system should be studied since the streets where traffic intensity is lower are mostly streets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One source of Pb is the resuspension of Pb [58], where it can accumulate in places such as windows, sidewalks, balconies, etc. This aspect should be taken into account when studying the influence that Pb can have on health since it is a highly toxic element and has no function in any organism [10]. To reduce this risk, a cleaning system should be studied since the streets where traffic intensity is lower are mostly streets.…”
Section: Discussionmentioning
confidence: 99%
“…There are also metals that have no function and are toxic in small quantities, such as Hg, Pb or Cd [10]. Relevant studies have shown that potentially toxic elements (PTEs) in road dust have negative effects on human health, such as poisoning, cancer, respiratory diseases and even psychological diseases [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…La carencia de respuesta del cultivo al fertilizante de azufre ocurre en la mayoría de las veces. El resultado es la presencia de sulfatos en el subsuelo u óxidos de azufre, que constituyen uno de los principales gases emitidos en las ciudades principalmente por actividades industriales, vehículos automotores y quema de biomasa (Alcalá et al, 2008). Aunque tanto las formas orgánicas como el sulfuro pueden contribuir a la nutrición vegetal en el tiempo, las plantas absorben del suelo primeramente el azufre en la forma de SO 4 = (Leustek y Saito, 1999).…”
Section: Sulfatosunclassified